Konsep Kebahagiaan menurut Surat Ali Imran Ayat 200 - Triyono, Agus; Santosa, Joko; Sumiran, Sumiran (Lembaga Yasin AlSys, 2025)
Happiness is the ultimate goal of human life and the subject of philosophical, psychological, and spiritual inquiry. In the Islamic perspective, happiness encompasses both worldly and hereafter dimensions. Surah Ali Imran verse 200 provides comprehensive guidance through four main pillars—ṣabr (patience), ṣabāt (steadfastness), murābaṭah (readiness for striving), and taqwā (piety)—which serve as the foundation for attaining true happiness. This study aims to explore the concept of happiness according to the Qur’an with a focus on Surah Ali Imran verse 200, and to analyze its relevance to modern life. Using a qualitative approach and thematic exegesis method, the study finds that happiness in Islam originates from obedience, perseverance in striving, and firm faith in Allah SWT. These spiritual values serve as the foundation for building a peaceful, balanced, and meaningful life, both in this world and in the hereafter.